2013
DOI: 10.1080/00981389.2013.827143
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Through the Silence: The Experience of Living With HIV-Positive Serostatus, and Its Implications on Disclosure

Abstract: AIDS has reached pandemic proportions and despite advances in medical treatment both the medical and social consequences of HIV-positive serostatus continue to be of concern throughout the world. In countries with greater access to antiretroviral therapy (ARV), HIV/AIDS it is no longer defined as fatal, but rather a chronic disease, thereby this study seeks to understand the experience of individuals living with HIV-positive serostatus, a multifaceted disease, from the time the infection is diagnosed through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…The lived experiences of the participants in this study revealed that living with HIV is an ongoing challenge, often accompanied by emotional turmoil, suffering, and shame. The findings of extant literature about living with HIV are consistent with the experience of the participants in this study (Feigin, Sapir, Patinkin, & Turner, 2013;Rouleau, Côté, & Cara, 2012).…”
Section: More Than a Chronic Diseasesupporting
confidence: 87%
“…The lived experiences of the participants in this study revealed that living with HIV is an ongoing challenge, often accompanied by emotional turmoil, suffering, and shame. The findings of extant literature about living with HIV are consistent with the experience of the participants in this study (Feigin, Sapir, Patinkin, & Turner, 2013;Rouleau, Côté, & Cara, 2012).…”
Section: More Than a Chronic Diseasesupporting
confidence: 87%
“…Many women reported that they found it hard to disclose their status and did not anticipate gaining any real value from it. Disclosure has traditionally been poor in South Africa and was marred by issues of stigma (Dlamini et al, 2009; Feigin, Sapir, Patinkin, & Turner, 2013; Simbayi et al, 2007). Lack of disclosure was accentuated by the large percentage of patients (60%) in our study who did not know how they acquired HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Human immunodeficiency virus (HIV) is a communicable disease, and disclosure of one's HIV status has been an important component of preventing onwards transmission. Since the development of effective medical treatment, HIV disclosure has become all the more important as people living with HIV (PLWH) can now expect to live a normal lifespan; disclosure now represents a fundamental and ongoing part of living with the disease (Feigin, Sapir, Patinkin, & Turner, 2013). HIV disclosure represents a form of psychological adjustment to a HIV+ diagnosis (Rodkjaer et al, 2014), as well as acting as a gateway for further social (Mburu et al, 2014), medical (Elopre et al, 2015;Ostermann et al, 2015) and emotional support (Yonah, Fredrick, & Leyna, 2014), and improved quality of life (Mutabazi-Mwesigire, Seeley, Martin, & Katamba, 2014).…”
Section: What Does This Study Add?mentioning
confidence: 99%